Red zones: criminal law and the territorial governance of marginalized people - Sylvestre, Marie-Ève (Cambridge University Press, 2019)
Navigating the territories of the law -- Law and territory, a legal geography -- Recognizances to keep the peace and be of good behaviour : the legal history of red zones and conditions of release -- Territory widening -- The shifting and expanding terrain of criminal justice management -- Territorializing : how legal territory is made and justified -- Conditional life inside the red zone -- Red zoning politics -- Red zones in and out of the courtroom.